Justification of Geotechnology for Complex Extraction of Useful Components from Overlying Rocks of the Uzbek Kumir Coal Mine (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article provides information on the extraction technology of the necessary and useful components located in the cover rocks of the UzbekCoal mine and information on which part and at which points the necessary components are present in this mine.